On the Localized Extreme Rainfall over the Great Bay Area in South China with Complex Topography and Strong UHI Effects - Sun, Xiaoyan; Luo, Yali; Gao, Xiaoyu; Wu, Mengwen; Li, Mingxin; Huang, Ling; Zhang, Da-Lin; Xu, Haiming (Monthly weather review, 2021)
In this study, high-resolution surface and radar observations are used to analyze 24 localized extreme hourly rainfall (EXHR; >60 mm h −1 ) events with strong urban heat island (UHI) effects over the Great Bay Area (GBA) in South China during the 2011–16 warm seasons. Quasi-idealized, convection-permitting ensemble simulations driven by diurnally varying lateral boundary conditions, which are extracted from the composite global analysis of 3–5 June 2013, are then conducted with a multilayer urban canopy model to unravel the influences of the UHI and various surface properties nearby on the EXHR generation in a complex geographical environment with sea–land contrast, topography, and vegetation variation. Results show that EXHR is mostly distributed over the urban agglomeration and within about 40 km on its downwind side, and produced during the afternoon-to-evening hours by short-lived meso- γ - to meso- β -scale storms. On the EXHR days, the GBA is featured by a weak gradient environment with abundant moisture, and a weak southwesterly flow prevailing in the boundary layer (BL). The UHI effects lead to the development of a deep mixed layer with “warm bubbles” over the urban agglomeration, in which the lower-BL convergence and BL-top divergence is developed, assisting in convective initiation. Such urban BL processes and associated convective development with moisture supply by the synoptic low-level southwesterly flow are enhanced by orographically increased horizontal winds and sea breezes under the influence of the herringbone coastline, thereby increasing the inhomogeneity and intensity of rainfall production over the “Π-shaped” urban clusters. Vegetation variations are not found to be an important factor in determining the EXHR production over the region.